Comparison of Environmental Conditions Surrounding the 2005 and 2006 Atlantic Hurricane Seasons - Clemente, Laura (2009)
The 2005 North Atlantic Hurricane season resulted in 28 named tropical cyclones (TCs), placing this season in the record books as the strongest and most costly Atlantic Hurricane season on record. The 2006 North Atlantic Hurricane season was expected to be almost as strong as the 2005 season, but instead resulted in an average season with 10 named TCs. Numerous factors are involved in the genesis and lifecycle of a TC. This research explores the tropical system as a whole, with the goal of understanding each of the factors that play a role in TC genesis. The objective of this study is to determine if there was a particular variable that played a significant role. This study will pave the way for future research on Hurricane seasons and the potential effects of Saharan dust on the genesis and lifecycle of TCs in the North Atlantic region. To achieve this objective, observations and analysis fields are used to examine environmental factors important to TC behavior, such as sea surface temperature (SST), mid-tropospheric moisture, atmospheric stability, and vertical wind shear. Saharan dust is studied as it has been a topic in recent literature and the role it plays in the tropical system is yet uncertain. The results indicate that warmer waters across the Main Development Region (MDR) along with favorable winds coming off the west of Africa mainly produced active hurricane season in 2005 as compare to 2006. Other environmental factors, such as lower wind shear (changing winds with height), existence of a moist mid-tropospheric layer and moist instability, were also partially the cause of the active 2005 hurricane season. More importantly, the results also indicated that Saharan Air Layer (SAL) interaction with TCs may be another environmental factor that influences TC activity. Therefore, SAL interaction with TCs may be yet another important piece of the puzzle in advancing our understanding of TC activity and intensity change in the Atlantic basin that demands further comprehensive research.